A Ground book on engineering mathematics Vol-1 - Mukherjee, Arup Kumar (Shreedhar Prakashani, 2014)
A Ground book on engineering mathematics Vol-1 / Mukherjee, Arup Kumar. -- Kolkata: Shreedhar Prakashani, 2014 510 M941v1 No. of Copies : 1